Fatores associados a infecções pulmonares em transplantados Renais e rim-pâncreas: um estudo caso-controle - Leonardo Meira de Faria (2020)
Kidney transplantation is an efficient treatment for end-stage renal disease. Due to the state of prolonged immunosuppression and environmental exposures, infectious complications are relatively common, notably lower respiratory tract infections. Data in the national literature are scarce regarding risk factors associated with pulmonary infections in these patients. The present case-control study, in the proportion 1: 1.8, matched by sex, age group, and type of donor (living or deceased donors), carried out in a reference kidney transplant hospital in the State of Minas Gerais - Hospital Felício Rocho from December 2017 to March 2020. The main objectives were to study the etiology and factors associated with lung infections in kidney transplant patients, in addition to identifying in the sample of kidney transplant patients, specific subgroups with increased risk of lung infections and proposal end of systematic approach to renal transplant recipients with acute pulmonary opacity.197 patients were included, 70 from the case group and 127 from the control group. The mean age was 55 and 53 years in the case and control group, respectively, with a male predominance in both groups. Most of the etiologies of previous kidney disease were undetermined in both groups. Among the etiologies identified, there was a higher proportion of diabetes mellitus for the cases (17.1%) and for the glomerulopathy controls (23%) followed by diabetes mellitus (22.2%). Patients in the case group had a significantly lower body mass index (BMI) when compared to controls (p = 0.013).In the sample studied, among the classes of immunosuppressants used, the use of corticosteroids in 67 cases and 106 controls was associated with an increased risk of infection (OR: 4.4 - 95% CI: 1.3 - 15.4), as well as the presence of bronchiectasis (9 cases and 3 controls; OR: 6.1 - 95% CI: 1.6 to 23.2). In the analysis of the isolated case patients, the predominance of ground-glass manifestation was observed in approximately 50% of the patients in the radiological parameter. Regarding the infectious etiology, the high prevalence of fungal agents (21.4%) stands out, the most prevalent being Histoplasma capsulatum (5 cases), Cryptococcus neoformans and Paracoccidioides brasiliensis, both with 3 cases. Cytomegalovirus was diagnosed in 14.3% of the case patients. In the present study involving adult renal transplant patients, the use of corticosteroids and the presence of bronchiectasis were associated with the occurrence of pulmonary infections in these patients. Unlike previous studies in the general population, low nutritional level was not related to an increased risk of pulmonary infections in this population. The need for careful follow-up of renal transplant patients is highlighted, with actions in the pre- and post-transplantation aiming at the adequate identification of those most at risk for pulmonary infectious complications. Patients in the case group had a significantly lower body mass index (BMI) when compared to controls (p = 0.013).In the sample studied, among the classes of immunosuppressants used, the use of corticosteroids in 67 cases and 106 controls was associated with an increased risk of infection (OR: 4.4 - 95% CI: 1.3 - 15.4), as well as well as the presence of bronchiectasis (9 cases and 3 controls; OR: 6.1 - 95% CI: 1.6 to 23.2). In the analysis of the isolated case patients, the predominance of ground-glass manifestation was observed in approximately 50% of the patients in the radiological parameter.